Strong convergence of a modified iterative algorithm for hierarchical fixed point problems and variational inequalities - Wang, Yuanheng; Xu, Wei (Fixed point theory and applications (Hindawi Publishing Corporation), 2013)
This article aims to deal with a new modified iterative projection method for solving a hierarchical fixed point problem. It is shown that under certain approximate assumptions of the operators and parameters, the modified iterative sequence { x n } converges strongly to a fixed point x ∗ of T , also the solution of a variational inequality. As a special case, this projection method solves some quadratic minimization problem. The results here improve and extend some recent corresponding results by other authors. MSC: 47H10, 47J20, 47H09, 47H05.